Senp2 expression was induced by chronic glucose stimulation in INS1 cells, and it was required for the associated induction of Ccnd1 and Mafa. Issue 6 (1st November 2016) - Jung, Hye Seung; Kang, Yu Mi; Park, Ho Seon; Ahn, Byung Yong; Lee, Hakmo; Kim, Min Joo; Jang, Jin Young; Kim, Sun-Whe
ABSTRACT: Post-translational modification by bonding of small ubiquitin-like modifier (SUMO) peptides influences various cellular functions, and is regulated by SUMO-specific proteases (SENPs). Several proteins have been suggested to have diverse impact on insulin synthesis and secretion through SUMO modification in β cells. However, the role of SUMO modification in β cell mass has not been established. Here, we examined the changes in expression of Senp in INS1 cells and pancreatic islets under diabetes-relevant stress conditions and associated changes in β cell mass. Treatment with 25 mM glucose for 72 h induced Senp2 mRNA expression but not that of Senp1 in INS1 cells. Immunohistochemical staining with anti-SENP2 antibody on human pancreas sections revealed that SENP2 was localized in the nucleus. Moreover, in a patient with type 2 diabetes, SENP2 levels were enhanced, especially in the cytoplasm. Senp2 cytoplasmic levels were also increased in islet cells in obese diabetic mice. Cell number peaked earlier in INS1 cells cultured in high-glucose conditions compared to those cultured in control media. This finding was associated with increased Ccnd1 mRNA expression in high-glucose conditions, and siRNA-mediated Senp2 suppression abrogated it. Mafa expression, unlike Pdx1, was also dependent on Senp2 expression during high-glucose conditions. In conclusion, Senp2 may play a role in β cell mass in response to chronic high-glucose through Cyclin D1 and Mafa.